2009
DOI: 10.1007/s11671-009-9482-8
|View full text |Cite
|
Sign up to set email alerts
|

New Bending Algorithm for Field-Driven Molecular Dynamics

Abstract: A field-driven bending method is introduced in this paper according to the coordinate transformation between straight and curved coordinates. This novel method can incorporate with the periodic boundary conditions in analysis along axial, bending, and transverse directions. For the case of small bending, the bending strain can be compatible with the beam theory. Consequently, it can be regarded as a generalized SLLOD algorithm. In this work, the bulk copper beam under bending is analyzed first by the novel ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Nowadays, it is still a challenge to study the mechanics of nanomaterials by means of experimental tests due to the difficulties encountered on the nanoscale. Therefore, the theoretical methods such as atomistic simulations and continuum mechanics theories are often used to analyze the bending, buckling and dynamic responses of nanostructures [Reddy (2007); Chen et al (2010); ; Roque et al (2011)].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is still a challenge to study the mechanics of nanomaterials by means of experimental tests due to the difficulties encountered on the nanoscale. Therefore, the theoretical methods such as atomistic simulations and continuum mechanics theories are often used to analyze the bending, buckling and dynamic responses of nanostructures [Reddy (2007); Chen et al (2010); ; Roque et al (2011)].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Detailed time-resolved studies of dynamics showed that the characteristic timescale of laserinduced exchange bias quenching in a polycrystalline Co/IrMn bilayer is 0.7 ± 0.5 ps, attributing the rapid decrease in exchange coupling to a spin disorder at the interface created by laser heating. [17] In our case, the demagnetization and switching dynamics after a 40 fs laser pulse illumination of the annealed IrMn(5)/Co 77 Gd 23 (4) sample have been studied as a function of time for various laser fluences (Figure 3a) and for different applied fields intensities (Figure 3b). A Co demagnetization time of ≈700 fs could be measured, which is independent of the applied field.…”
Section: Exchange Bias Switchingmentioning
confidence: 99%
“…First, single-pulse laser switching experiments have been performed by exciting an IrMn(5)/Co 77 Gd 23 (4) sample from the top CoGd surface (Figure 1a). Using a single laser pulse of 40 fs with a fluence of 17 mJ cm -2 , induces a reversal of the exchange field from 154 to −26 mT, as reported in Figure 2a.…”
Section: Stacks Structure and Single-shot Exchange Bias Switchingmentioning
confidence: 99%
See 1 more Smart Citation